PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEBSITE - Soulisa, Dinda Irdayani (SOSCIED, 2025)
The school library functions as a learning resource center that supports the educational process and enhances students' literacy. However, in many schools, including SMP Negeri 7 Kota Sorong, library management is still conducted manually, resulting in slow services and difficulties in data recording. This study aims to design a web-based library information system to address these issues. The research method used is the Research and Development (R&D) method, which includes stages of needs analysis, system design, implementation, and testing. The results of the design show that the developed system is capable of managing book data, members, borrowing transactions, and activity reports efficiently. This system is expected to assist library staff in managing data and improving services for students.